Coupled-Inductors Boost Converter With Quasi-Square-Wave Zero-Voltage-Switching - Mahmoud Nassary; Enric Vidal-Idiarte; Ignacio Galiano Zurbriggen; Oswaldo Lopez-Santos; Javier Calvente (IEEE Open Journal of Power Electronics)
In this article, the Quasi-Square-Wave (QSW) mode with Zero-Voltage Switching (ZVS) in the Coupled Inductors Boost (CIB) converter is thoroughly analyzed to provide design guidelines and compare the obtained performance with the QSW-ZVS boost converter. The studied mode is used to enforce output voltage regulation employing a nested loop architecture with an inner current loop and an outer voltage loop providing the reference for the inner loop. The current controller is an innovative hysteresis control in which the upper limit compares the secondary inductor current with the reference provided by the outer loop and the lower limit compares the primary inductor current with a constant value defined to ensure ZVS. This configuration allows the elimination of the right-half-plane zeros inherently widening the bandwidth of the frequency response. As it is demonstrated, the CIB exhibits two times faster dynamic response in front of load perturbations at the cost of a small reduction of the efficiency at high power loads and the inclusion of two additional components. Theoretical predictions and feasibility of the QSW-ZVS CIB are confirmed by means of simulated and experimental results.